New Land, New Life : A Success Story of New Land Resettlement in Bangladesh. - Jenkins, Andrew. (CAB International, 2020)
The Ganges-Brahmaputra-Meghna deltas has newly emerged 'char' islands, which are very vulnerable, socially, institutionally and environmentally. This book explains how the Governments of Bangladesh and the Netherlands cooperated on a land-based rural development project to give settlers security and purpose.